ANALISIS CAMPUR KODE DALAM PEMBELAJARAN DARING SISWA SEKOLAH DASAR - Sagi Winoto (COLLASE (Creative of Learning Students Elementary Education), 2022)
AbstractThis study aims to background of code-mixing describe the form of code-mixing and function of code-mixing the teacher learning  in class VI primary school.   This research uses descriptive qualitative research design. Subjects in this study is a first grade teacher. The data collection method is observation, interviews and documentation. Observation and interviews methods used to find the data forms and types of code-mixing used by teachers, while documentation methods used to find the data background factors causing the teacher did not mix code. The results showed that the mixed form of code used by teachers is a form of words, phrases, and clauses. Mixed types of code that teachers do is code-mixing and code-mixing into the outside. Factors that cause teachers to use mixed code is (1) the factors of limited user codes, (2) factors speaker and personal speaker, (3) factors conversation partner, (4) the factors of functions and objectives, and (5) use factors more popular term ,